Influence of electrolyte composition on the microstructure and photocatalytic activity of TiO2 nanostructures - DEMİRCİ, SELİM (SPRINGER, 2022)
In this study, titanium dioxide (TiO2) nanostructures were produced on pure titanium in different electrolytes at constant voltage of 20 V for 30 min. The crystallographic structure, surface morphology, and optical properties of the films were investigated by XRD, SEM, and UV-vis spectrum, respectively. The wettability of the samples was determined by contact angle measurement equipment. The photocatalytic properties of the TiO2 films were tested by the degradation of a methylene blue (MB) as the model reaction under UV light irradiation. The results showed that the electrolyte composition can play an important role in the surface morphology of nanostructured TiO2 films and therefore on various properties such as optics, electronics, sensing, and degradation. The SEM images of the samples demonstrated that surface morphology was directly affected by the electrolyte composition. It is known that the surface area is a dominant factor affecting the photocatalytic activity of a porous TiO2 layer prepared by anodic oxidation. The TiO2 film (sample C) anodized in 1 M Na2SO4 containing 5 wt.% NH4F exhibited better photocatalytic performance as compared to the other oxide films. This is because a higher surface area with dense pore structure favors more photocatalytic active areas. The photocatalytic degradation efficiency of MB using sample C was reached to 92.35% and rate constant 5.92 x 10(-3), respectively. Moreover, this sample showed lowest band gap energy that was almost 3.167 eV. We believe that new anodic TiO2 nanoporous structures are highly promising in photocatalytic decomposition of water and pollutants elimination.
Keywords: TiO2 film; Electrolyte type; Surface morphology; Contact angle and photocatalytic activity; NANOTUBE ARRAYS; METHYLENE-BLUE; DEGRADATION; TITANIUM; NANOPARTICLES; FABRICATION; PARTICLES; ANATASE; GAS